Leadership Matters: Elementary Self-Contained Autism Special Education Teachers’ Perceptions of Administrator Support - Dye, Kasey; Bowman, Rachel Walker (Journal of the American Academy of Special Education Professionals, 2024)
There is a national shortage of special education teachers, so it is imperative to retain special educators in the field (Carver-Thomas & Darling-Hammond, 2017). The most commonly cited reason special education teachers shared for leaving is lack of support from their administration. The purpose of this qualitative study was to explore how special education teachers of self-contained grades 3-5 classes of children with Autism Spectrum Disorders perceive the level of support provided by their school-based administrators and the influence of their school-based administrators on their experience of job satisfaction. Through individual interviews with three teachers, the researchers found that self-contained special educators’ perceived levels of support provided by school-based administrators varied based on administrators’ special education knowledge, communication, advocation, follow-through, and treatment of special educators as professionals. The other primary finding was that school-based administrators can positively or negatively influence self-contained special education teachers’ job satisfaction. The researchers discussed the implications of these findings.